Improved Electrical Performance of Perovskite Photovoltaic Mini‐Modules through Controlled PbI2 Formation Using Nanosecond Laser Pulses for P3 Patterning. Issue 4 (24th February 2021) - Fenske, Markus; Schultz, Christof; Dagar, Janardan; Kosasih, Felix Utama; Zeiser, Andreas; Junghans, Cornelia; Bartelt, Andreas; Ducati, Caterina; Schlatmann, Rutger; Unger, Eva; Stegemann, Bert
Abstract : The upscaling of perovskite solar cells to modules requires the patterning of the layer stack in individual cells that are monolithically interconnected in series. This interconnection scheme is composed of three lines, P1–P3, which are scribed using a pulsed laser beam. The P3 scribe is intended to isolate the back contact layer of neighboring cells, but is often affected by undesired effects such as back contact delamination, flaking, and poor electrical isolation. Herein, the influence of the laser pulse duration on the electrical and compositional properties of P3 scribe lines is investigated. The results show that both nanosecond and picosecond laser pulses are suitable for P3 patterning, with the nanosecond pulses leading to a higher open circuit voltage, a higher fill factor, and a higher power conversion efficiency. It is found that the longer pulse duration resultes in a larger amount of PbI2 formed within the P3 line and a thin Br‐rich interfacial layer which both effectively passivate defects at the scribe line edges and block charge carrier in its vicinity. Thus, nanosecond laser pulses are preferable for P3 patterning as they promote the formation of beneficial chemical phases, resulting in an improved photovoltaic performance. Abstract : P3 patterning for serial interconnection of perovskite solar cells by nanosecond (ns) and picosecond laser pulses is investigated. Both pulse durations are suitable, but ns pulses enable an improved current–voltage behavior, due to the formation of PbI2 and a Br‐rich interfacial layer, which both effectively passivate defects and block charge carriers in the scribe line vicinity.